Characteristics of Manuscripts Dictionary of Mu'jam Al-Qur'an Collection of Research and Development Center for Lectures and Religious Treasures Ministry of Religion of the Republic of Indonesia - Ridhoul Wahidi; Wahidi, Ridhoul; Nur Kholis; M. Nurkhalis. AM (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
This article examines the manuscript Kamus Mu’jam al-Qur’an, a collection of the Ministry of Religious Affairs of the Republic of Indonesia. The manuscript is not merely a source of religious texts, but it also embodies certain characteristics that reflects the history, traditions and values encapsulated within it. This study aims to describe the characteristics of the manuscript using philology as the primary method, with codicology and textology as the two main approaches. The codicological aspects of this manuscript indicates that Kamus Mu’jam Al-Qur’an encompasses vocabulary found in the Qur’an. It is written in Arabic and consists of a single piece with 37 pages. The manuscript, threaded and non-uniform in paper and text size (21 x 17 cm), employs khat naskhi with black ink as the primary color, while certain marks utilize green and red ink. Additionaly, textual aspects of it describes Kamus Mu’jam al-Qur’an including several scholia, such as corrections for written errors, vocabulary, letter descriptions, reading marks, wakaf signs and lists of invalid texts. The major finding of this study is the eight keywords: al-Asrār, dīnu yusr, ihsān, abrār, sulḥ, ‘ilm, ‘adamu taqlīd, and al-‘amal that were not typical to other dictionaries. This study contributes significantly by providing fresh insights into the importance of the Kamus Mu’jam al-Qur’an as a source of knowledge and understanding how this manuscript has been preserved over time. It also sheds light on the evolution of Quranic studies in Indonesia.